Determinants of money supply in Nigeria - Aderopo R. Adediyan (CBN Journal of Applied Statistics, 2020)
Studies on money supply determinants focus on the Classicists or Monetarists, Key-nesians and post-Keynesians variables like income and money multiplier. This re-search extends the literature on money supply determinants to include the influ-ence of financial liberalization on money supply with a reference to Nigeria between1980 and 2019, using the Autoregressive Distributed Lag (ARDL) approach. Dataused for the study were collected from the 2019 CBN Annual Statistical Bulletin.The study found that financial liberalization is an important factor in determiningmoney supply in Nigeria, in addition to currency ratio, required reserve ratio andhigh-powered money. As a result, the extent of the liberalization of the financialsector matters in decisions on the regulation of money supply in the economy.
Keywords: E5; E51; E52; 330; Autoregressive distributed lag; financial liberalization; money supply determi-nants